2004
DOI: 10.1111/j.1440-1673.2004.01280.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcified nodal metastasis from squamous cell carcinoma of the head and neck

Abstract: Calcification within cervical lymph nodes is relatively rare, and most commonly ascribed to benign inflammatory or infectious processes. We present a case of a calcified submandibular nodal metastasis from squamous cell carcinoma of the lip and review the current published literature on nodal calcifications in the neck. To the authors' knowledge, calcification resulting from metastatic squamous cell carcinoma of the head and neck has been described only once previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 10 publications
1
12
1
Order By: Relevance
“…2,4 Microcalcifications in metastatic papillary thyroid carcinoma have been reported to be as high as 68.7%. 5 Hodgkin lymphoma is the most common cause of nodal calcifications in treated (chemotherapy or radiation therapy) malignancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,4 Microcalcifications in metastatic papillary thyroid carcinoma have been reported to be as high as 68.7%. 5 Hodgkin lymphoma is the most common cause of nodal calcifications in treated (chemotherapy or radiation therapy) malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Metastatic SCC of the head and neck manifesting as calcified cervical lymph nodes is exceedingly rare. 2,4 To the best of our knowledge, there has been no report of the sonographic findings of calcified cervical nodes from SCC. In this report, we present 2 cases of cal-cified cervical nodes with pathologically proven metastatic SCC: 1 case showing diffuse calcifications without internal color Doppler flow and the other containing multifocal punctate calcifications with internal flow.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Baskota et al [35] reported that in patients with tuberculous cervical lympadenitis, the majority of the nodes are unilateral; of these, only one group of lymph nodes is usually involved. It was also reported that calcification in tuberculous neck nodes is much less common than calcification in nodes elsewhere in the body [31]. The case presented here is very unusual because the lesions were in jugular, supraclavicular, and posterior cervical lymph node chains, and were both bilateral and multiple.…”
Section: Discussionmentioning
confidence: 78%
“…It was reported that the most common neoplastic cause of nodal calcification in the neck is thyroid tumors [31,32]. However, Gormly and Glastonbury [31] also reported a case of calcified submandibular nodal metastasis resulting from squamous cell carcinoma of the lip, and head -neck squamous cell carcinomas must be considered during differential diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation